Perancangan Sistem IoT Untuk Monitoring Getaran dan Stress Pada Kanopi Rumah Berbasis ESP32 - Raushan Dhamir; Mhd. Basri (LKP Unity Academy, 2025)
The development of Internet of Things (IoT) enables real-time and continuous monitoring systems. Lightweight structures such as house roofs or canopies are vulnerable to environmental and load changes, yet monitoring is still commonly performed manually, making early detection difficult. This study aims to design and implement an IoT-based canopy structure monitoring system using ESP32 integrated with an MPU6050 vibration sensor, a load cell with HX711 module, and a DHT22 temperature and humidity sensor. Measurement data are transmitted via WiFi to a server for database storage and visualization through a web-based dashboard. Furthermore, the collected data are processed using the Relative Corrosion Potential Index (IPKR), calculated based on normalized parameters including temperature, humidity, vibration, and load variation. The results show that the system is capable of performing real-time data acquisition, transmission, and visualization effectively. The system also provides structural condition indicators based on IPKR values classified into safe, warning, and danger categories. Therefore, the developed system can serve as an effective and informative early monitoring solution for detecting changes in lightweight structure conditions.